Banking Interest in the Contemporary Jurist’s Perspective: A Yusuf Al-Qaradawi’s Economics Thought - Yuli Utami (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2014)
Al-Qaradawi’s contribution to the development of contemporary Islamic economics is very profound. Many Muslim economists subscribe to his opinions, and some banking institutions and insurance companies have even adopted his views as their general policies. It is very unfortunate, however, that such a great contribution has not been well researched. It is the intention of this research to fill up this lacuna by making it accessible to the prospective readers. The objective of this study is mainly to introduce Al-Qaradawi’s economic thought and its relevance to contemporary development of Islamic economics discourse. For this purpose, the research attempts to shed some light on selected contributions that he has made to the current discourse of interest in the banking system. In connection to this, his conceptions and approaches to issues and problems in contemporary Islamic economics are also explored. It argues that Al-Qaradawi’s works on Islamic economic missed the empirical test to provide evidence of the strength and the reliability of his data theories and concepts, particularly on the topic of zakat, poverty and environment. Keywords: interest, Islamic economics, Yusuf Al-Qaradawi, Islamic legal thought